2007
DOI: 10.1128/aem.02242-06
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157:H7 Colonization at the Rectoanal Junction of Long-Duration Culture-Positive Cattle

Abstract: Long-duration consistently Escherichia coli O157:H7 culture-positive cattle were euthanized and necropsied. Tissue and digesta from along the gastrointestinal tract (GIT) were cultured for the bacteria and examined histologically for lymphoid character. E. coli O157:H7 was detected only at the rectoanal junction mucosa and not at any other GIT location.Escherichia coli O157:H7 causes hemorrhagic colitis and the life-threatening sequela hemolytic-uremic syndrome in humans (6). Healthy cattle are the major reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 12 publications
4
80
0
Order By: Relevance
“…In contrast, Shiga toxins do not affect either EHEC O157:H7 colonization of the terminal rectum in single strain rectal challenged cattle (Sheng et al 2006) or secretory responses in bovine ileal intestinal loops from older calves (Stevens et al 2002). The terminal rectum studies (Naylor et al 2003;Sheng et al 2004Sheng et al , 2006Low et al 2005;Lim et al 2007) have focused on the role of lymphoid tissue in the EHEC O157:H7 infection process in cattle without comparisons with absorptive epithelium in other intestinal sites despite the reported association of EHEC O157:H7 with small and large intestinal sites in challenged cattle (Cray and Moon 1995;Grauke et al 2002;Van Baale et al 2004). In a previous study, we reported that there were no differences in the dose-dependent colonization of small and large intestinal sites compared with the terminal rectum (Baines et al 2008, manuscript in preparation) and in this study, we add to this by showing that the small and large intestinal tissues also respond to EHEC O157:H7 secreted cytotoxins in a similar manner to that reported for a model system purported to better represent the response of ruminant systems to EHEC O157:H7 colonization (Robinson et al 2006).…”
Section: Ivoc Adherence Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Shiga toxins do not affect either EHEC O157:H7 colonization of the terminal rectum in single strain rectal challenged cattle (Sheng et al 2006) or secretory responses in bovine ileal intestinal loops from older calves (Stevens et al 2002). The terminal rectum studies (Naylor et al 2003;Sheng et al 2004Sheng et al , 2006Low et al 2005;Lim et al 2007) have focused on the role of lymphoid tissue in the EHEC O157:H7 infection process in cattle without comparisons with absorptive epithelium in other intestinal sites despite the reported association of EHEC O157:H7 with small and large intestinal sites in challenged cattle (Cray and Moon 1995;Grauke et al 2002;Van Baale et al 2004). In a previous study, we reported that there were no differences in the dose-dependent colonization of small and large intestinal sites compared with the terminal rectum (Baines et al 2008, manuscript in preparation) and in this study, we add to this by showing that the small and large intestinal tissues also respond to EHEC O157:H7 secreted cytotoxins in a similar manner to that reported for a model system purported to better represent the response of ruminant systems to EHEC O157:H7 colonization (Robinson et al 2006).…”
Section: Ivoc Adherence Assaymentioning
confidence: 99%
“…EHEC O157:H7 has been isolated from the small and large intestine of older calves and mature cattle but not necessarily associated with A/E lesions (Cray and Moon 1995;Brown et al 1997;Grauke et al 2002;Naylor et al 2003;van Baale et al 2004). The current model for EHEC O157:H7 colonization in cattle suggests that the lymphoid-follicle dense mucosa in the terminal rectum is the primary colonization site and it is this colonization that is responsible for persistent shedding (Naylor et al 2003Sheng et al 2004Sheng et al , 2006Lim et al 2007). The basic assumption of this model is that cattle are not adversely affected by EHEC O157:H7 virulence factors, and although a reduction in the expression of some EHEC O157:H7 virulence factors has been demonstrated (Rashid et al 2006), it is not true for all virulence factors.…”
mentioning
confidence: 99%
“…The average duration of STEC O157 carriage is 30 days; however, in rare cases animals may be colonized for up to 1 year (28). Animals excreting greater than 10 4 CFU/g feces are termed "super-shedding animals" (29,30).…”
Section: Animal Species Of Importance In the Epidemiology Of Stec Cattlementioning
confidence: 99%
“…In this study, extensive histological examination of terminal rectal tissues did not reveal a prominent association between E. coli O157:H7 microcolonies and follicle-associated epithelium. Thus, the reason for the terminal rectum tropism of E. coli O157:H7 is still obscure (19). Two of the main features of this area are a potentially reduced width of the mucous barrier, based on measurements taken with mice over Peyer's patches (33) and the fact that the recto-anal junction is adjacent to the anal sphincter.…”
mentioning
confidence: 99%